Effects of Plantation Type and Soil Depth on Microbial Community Structure and Nutrient Cycling Function - Wang, Wenbo; Wang, Jianjun; Wang, Qianchun; Bermudez, Ramon Santos; Yu, Shihe; Bu, Pengtu; Wang, Zhanwei; Chen, Dongshen; Feng, Jian (Frontiers in Microbiology, 2022)
Declining soil quality and microecological imbalances were evaluated in larch plantations in this study. One potential solution to this problem is the cultivation of mixed coniferous and broad-leaved plantations. However, it is unclear whether and how soil microbial community structure and nutrient cycling function would be affected by mixed plantations and soil depths. In this study, we used high-throughput sequencing technology to investigate bacterial 16S and fungal ITS regions for comparisons of soil microbial diversity among forest types (a Larix gmelinii pure plantation, a Fraxinus mandshurica pure plantation, a Larix-Fraxinus mixed plantation within the Larix row, the Fraxinus row, and between the Larix and Fraxinus rows) and soil depths (0–10 cm, 10–20 cm, and 20–40 cm). These data were used to evaluate variations in microbial communities and nutrient cycling function with the determining environmental factors. Our results indicated that bacteria had a stronger spatial dependence than did fungi, while plantation types significantly affected the fungal community. The relative abundance of Rokubacteriales, as well as bacterial ligninolysis, nitrate ammonification and nitrite ammonification functions significantly decreased with increasing soil depth. Compared with other plantations, the relative abundance of Inocybaceae was significantly higher in the Larix plantation. Distance-based redundancy analysis (db-RDA) showed that Rokubacteriales and Inocybaceae abundances were positively correlated with pH, ammonium nitrogen content, available phosphorus content, and phosphatase activity. Our findings indicate that variations in soil available phosphorus are closely related to the relative abundances of Rokubacteriales at different soil depths and Inocybaceae in different plantation types. Mixed plantations might change the availability of soil phosphorus by controlling the relative abundance of Inocybaceae. We recommend that fungal community changes be considered in the sustainable management of mixed plantations.